Enhanced Performance Analysis of OFDM, Measuring Bit Error Rate and Peak to Average Power Ratio using Different Modulation - Sharma, Milind; Kumar, Shiv; Navlakha, Anlit (International Journal of Computer Sciences and Engineering, 2020)
Wireless communications is the fastest growing segment of the communication industry. The most common used wireless communication is mobile communication. But, there are many technical challenges that must be overcome. In A signal transmitted on a wireless channel is subject to Interference, Fading, Propagation path loss, Shadowing etc. There is always a greater order for capacity with the high quality service. In this situation, OFDM is well defined technique, which is a very much suitable option for high band width data transmission, by converting the wideband signal into narrow band signals for transmission. The transmission of these individual narrow band signals are executed with orthogonal carrier. In this dissertation, the performance of transmission mode are evaluated by Bit Error Rate versus the Signal to Noise Ratio under frequently used Rayleigh channel modes,. In order to investigate, first we derive the mathematical modeling for bit error rate and signal to noise ratio of OFDM over Rayleigh then, OFDM is design. now we have assumed Rayleigh fading channel as noise channel and also built BPSK, QPSK and QAM modulation technique. OFDM transmitters and receivers are implemented here using IFFT and FFT of size 64 with 52 sub carriers to convert the spectra to time domain & vice versa and also measure peak to average power ratio in different modulation scheme.